Faktor-Faktor yang Berhubungan dengan Lama Rawat Inap Pasien Tifoid di Rumah Sakit TK IV 020704 Bandar Lampung - Amelia Senja; Rini Palupi; Nopi Anggista Putri; Feri Kameliawati (Pelantar Press, 2026)
Typhoid fever is one of the most common infectious diseases in Indonesia and has potential complications that can prolong the duration of hospitalization. Length of hospitalization is influenced by various factors such as knowledge and personal hygiene. Identification of these factors is necessary so that the patient management process can be carried out more effectively. This study aims to determine the factors associated with the length of hospitalization of typhoid patients at Class IV Hospital 020704 Bandar Lampung. Using a cross-sectional design involving 59 respondents selected through accidental sampling technique. Data were collected in August-September 2025 using a questionnaire data analysis with the chi-square test with a significance level of p 0.05. The results showed that most patients were hospitalized for less than 6 days. There was a significant correlation between gender (p = 0.026), insurance coverage (p = 0.003), knowledge level (p = 0.026), and personal hygiene (p = 0.001) and length of stay. Low levels of knowledge and personal hygiene were associated with longer hospital stays. It can be concluded that gender, insurance coverage, knowledge level, and personal hygiene influence the length of stay for typhoid patients. Therefore, increasing health education and improving hygiene are crucial to accelerate patient recovery